Review: Palestine. From the Oslo Accords to Apartheid - Piñuela de las Heras, Alejandro (Anaquel de Estudios Árabes, 2024)
Review of the recent title: "Palestine: From the Oslo Accords to Apartheid," a work by the esteemed specialists in the field, Barreñada Bajo and Abu Tarbush, which rigorously dissects the disastrous path that the Palestinian-Israeli conflict has taken since Oslo and beyond. An important, relevant, and fresh work for addressing the conflict from a perspective aligned with sensitivity and empathy.